Agile Management Practices in Post-Pandemic Organizations: Enhancing Flexibility and Innovation - Supriatna, Ucu (Yayasan Kreatif Indonesia Emas, 2024)
The COVID-19 pandemic served as a global catalyst, accelerating the need for organizational adaptability and resilience in the face of unprecedented uncertainty and disruption. This study investigates the adoption and implementation of agile management practices within Indonesian firms in the post-pandemic era. It moves beyond the traditional application of agile in software development to explore its broader role in fostering organizational flexibility, enhancing cross-functional collaboration, and driving iterative innovation across various business functions. Through a qualitative case study methodology, which includes in-depth interviews with managers and team leads from a diverse range of organizations (startups, SMEs, and multinational corporations), and a comprehensive review of organizational reports, this paper identifies key success factors, persistent challenges, and the cultural nuances influencing agile transformation in an emerging market context. The findings reveal that while agile has gained significant traction, particularly in the tech sector, its broader institutionalization is hindered by cultural resistance, skill gaps, and short-term strategic thinking. Based on this analysis, the paper proposes a strategic model for sustainable agile transformation that is specifically tailored to the Indonesian business environment, emphasizing the importance of localized frameworks, leadership buy-in, and the creation of a psychologically safe, feedback-driven culture.